The Effect of Gentle Handling on Depressive-Like Behavior in Adult Male Mice: Considerations for Human and Rodent Interactions in the Laboratory. (6th March 2018) - Neely, Caroline; Lane, Christina; Torres, Julio; Flinn, Jane
Abstract : Environmental factors play a significant role in well-being of laboratory animals. Regulations and guidelines recommend, if not require, that stressors such as bright lighting, smells, and noises are eliminated or reduced to maximize animal well-being. A factor that is often overlooked is handling and how researchers interact with their animals. Researchers, lab assistants, and husbandry staff in animal facilities may use inconsistent handling methods when interacting with rodents, but humans should be considered a part of the animal's social environment. This study examined the effects of different handling techniques on depressive-like behavior, measured by the Porsolt forced swim test, in adult C57BL/6J male mice. The same two researchers handled the mice in a gentle, aggressive, or minimal (control) fashion over approximately two weeks prior to testing. The results demonstrated a beneficial effect of gentle handling: gentle handling reduced swimming immobility in the forced swim test compared to mice that were aggressively or minimally handled. We argue that gentle handling, rather than methodical handling, can foster a better relationship between the handlers and rodents. Although handling is not standardized across labs, consistent gentle handling allows for less challenging behavioral testing, better data collection, and overall improved animal welfare.